Agriculture Building construction showing interior framing, Alaska-Yukon-Pacific Exposition, Seattle, Washington, ca. 1908 - Curtis, Asahel, 1874-1941 (1908)
On verso of photograph: Agriculture Bldg. PH Coll 727.162 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number